The Influence of Store Atmosphere, Service Quality, and Location on Consumer Purchasing Decisions at Nugi Bali - Putu Indah Hapsari; I Gusti Ayu Agung Istri Sari Dewi; I Kadek Angga Saputra (Journal of Governance, Taxation and Auditing, 2026)
Previous studies have varied in their focus, and there is a lack of research on how shop atmosphere, service quality, and location affect consumers' choices to buy. Furthermore, sales fluctuations at Nugi Bali in Bangli Regency in 2025 were discovered as a study concern, suggesting that customers' purchase choices are still unstable. We want to learn a lot about how shop ambiance, service quality, and location influence customers' final purchases from this research. Using a combination of the strategy and procedure proposed by Hair et al. (2019) and purposive sampling, 102 participants were selected to participate in the study in Bangli Regency. We used multiple linear regression, t-tests, and F-tests to examine the data that came from the surveys. There is a positive and significant relationship between store atmosphere, service quality, and location in terms of customers' purchasing decisions at Nugi Bali. Moreover, the study found that (1) store atmosphere, (2) service quality, and (3) location all have a positive and significant effect on customers' purchasing decisions.